2014
DOI: 10.1007/s00248-014-0433-2
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Assemblages Associated with the Phyllosphere, Dermosphere, and Rhizosphere of Tree Species of the Atlantic Forest are Host Taxon Dependent

Abstract: Bacterial communities associated with tree canopies have been shown to be specific to their plant hosts, suggesting that plant species-specific traits may drive the selection of microbial species that comprise their microbiomes. To further examine the degree to which the plant taxa drive the assemblage of bacterial communities in specific plant microenvironments, we evaluated bacterial community structures associated with the phyllosphere, dermosphere, and rhizosphere of seven tree species representing three o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
1
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 29 publications
9
68
1
10
Order By: Relevance
“…Lower growth of untreated (control) seedlings when compared to growth in the other treatments was also observed ( Table 2), suggesting that the use of microorganisms promoted the development of caimito seedlings. Thus, it could be inferred that the associations of bacterial communities associated with the rhizosphere of fruit species are hosts dependent on the taxon, that is, on the species itself, as concluded by Lambais et al (2014), who studied the rhizosphere of arboreal species of the Atlantic Forest and showed that the bacterial communities associated to trees were specific to the hosts of plants.…”
Section: Resultsmentioning
confidence: 94%
“…Lower growth of untreated (control) seedlings when compared to growth in the other treatments was also observed ( Table 2), suggesting that the use of microorganisms promoted the development of caimito seedlings. Thus, it could be inferred that the associations of bacterial communities associated with the rhizosphere of fruit species are hosts dependent on the taxon, that is, on the species itself, as concluded by Lambais et al (2014), who studied the rhizosphere of arboreal species of the Atlantic Forest and showed that the bacterial communities associated to trees were specific to the hosts of plants.…”
Section: Resultsmentioning
confidence: 94%
“…The inhabitants of canopy soils depend on the tight cycling of limited resources, facilitated by a decomposer community adapted to the extremes in climate that characterise canopy habitats [6][7][8]. In terrestrial soils, microorganisms are known to drive decomposition [9], yet little is known about the abundance of microorganisms or their role in canopy soils [10][11][12][13]. Recent advances in canopy access have improved our understanding of tropical rain forests but information on canopy microbial communities is lacking [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Esses dados sugerem uma associação entre a história evolutiva das árvores e a comunidade microbiana sobre a filosfera (REDFORD et al, 2010;LAMBAIS et al, 2014). Embora a comunidade bacteriana associada à filosfera de diferentes espécies arbóreas seja altamente diversa, no nível de proteoma elas compartilham processos metabólicos essenciais para a colonização e crescimento sobre a superfície da folha, sugerindo alta redundância funcional (LAMBAIS et al, 2016-submetido para publicação).…”
Section: Microbioma Vegetalunclassified
“…Diversos trabalhos desenvolvidos na Mata Atlântica têm avaliado e descrito a composição e estrutura das comunidades microbianas associadas ao solo e filosfera de algumas espécies arbóreas (MONTENEGRO, 2012;LAMBAIS et al, 2014;LIMA-PERIM et al, 2016). No entanto, abordagens que permitam avaliar associações entre micro-organismos e sua importância para a estruturação das comunidades, como redes de co-ocorrência (BARBERAN et al, 2012;BATES et al, 2012) Os resultados mostraram que, nas filosferas das duas espécies de plantas nas diferentes florestas, Gammaproteobacteria e Alphaproteobacteria foram os grupos com maior número de conexões, sugerindo que podem estar associadas com funções centrais na filosfera, como descrito anteriormente por Remus-Emsermann e Vorholt (2015).…”
Section: Análises De Padrões De Co-ocorrênciaunclassified
See 1 more Smart Citation